Inside Cover: Bis(Cyclic Alkyl Amino Carbene) Ruthenium Complexes: A Versatile, Highly Efficient Tool for Olefin Metathesis (Angew. Chem. Int. Ed. 4/2017). Issue 4 (4th January 2017) - Gawin, Rafał; Kozakiewicz, Anna; Guńka, Piotr A.; Dąbrowski, Paweł; Skowerski, Krzysztof
Abstract : Unexpectedly high reactivity is observed for a bis(cyclic alkylaminocarbene) ruthenium complex, which allows the formation of terminal and internal C−C double bonds at very low catalyst loadings. In their Communication onpage 981 ff., K. Skowerski et al. show that turnover numbers exceeding 3×10 5 were achieved in the self‐metathesis of 1‐decene. Classical Grubbs and Hoveyda–Grubbs complexes were less selective and several times less efficient in this transformation.